(untitled) (Atlas Journal of Biology, 2017)
Determination of species within the genus Cannabis has important legal medical and social implications. Recent genome sequencing has shown that the genomes of C. sativa (recreational marijuana and hemp), C. indica (medical marijuana) and C. ruderalis (feral marijuana) can all be distinguished. However, hybridization among the species has occurred with widely varying outcomes in the percent of genome transmitted. The aim here was to determine if a simple assay based on the DNA sequence of ITS2 could be used to distinguish among species. Using sequences at GenBank as a reference eighteen plant samples were sequenced and shown to be identical to C. indica sequence and different from C. sativa and C. ruderalis at 4 positions within the 25S rRNA gene. This result and the geographic separation of the centers of genetic diversity argues strongly for polytypic origins of the 3 species. Analysis of interspecific hybrids sequences at GenBank suggested only the C. indica allele is transmitted preferentially. Finally, a SNP within the ITS could be used to distinguish two types within the eighteen plants. Therefore this simple genetic test can be used for rapid plant identification and to assist in strain identification.